Terrorism studies a reader - Horgan, John; Braddock, Kurt (Routledge, 2012)
This new Reader aims to guide students through some of the key readings on the subject of terrorism and political violence. In an age when there is more written about terrorism than anyone can possibly read in a lifetime, it has become increasingly difficult for students and scholars to navigate the literature. At the same time, courses and modules on terrorism studies are developing at a rapid rate. To meet this challenge, this wide-ranging Reader seeks to equip the aspiring student, based anywhere in the world, with a comprehensive introduction to the study of terrorism. Containing many of the most influential and groundbreaking studies from the world's leading experts, drawn from several academic disciplines, this volume is the essential companion for any student of terrorism and political violence. This Reader will be essential reading for students of Terrorism and Political Violence, and highly recommended for students of Security Studies, War and Conflict Studies and Political Science in general, as well as for practitioners in the field of counter-terrorism and homeland security.